Communication management under the spotlight: – A literature review - Grove Ditlevsen, Marianne; Johansen, Trine Susanne (Communication & Language at Work, 2019)
Purpose: Although communication management is a widely used term, little emphasis is given to understanding it as a concept in its own right. The paper aims to establish a foundation for acknowledging communication management as a distinct concept through charting its multiple understandings in order to identify its defining features. Design/methodology/approach: A systematic review of understandings of communication management in public relations, corporate communication, strategic communication, and integrated communication literature was performed. Out of a total of 113 sources 40 were reviewed through a narrative synthesis. Findings: There is widespread and ambiguous use of the term rooted in two main strands of literature and a third, less coherent, strand. In addition, the different understandings point to central features linking communication, management, and strategy. Theoretical and practical implications: To make fully use of the potential of communication management as a unifying concept within and across different communication fields, it is suggested to view it at the intersection of, and through the lenses of, the features identified as central to existing understandings of communication management, i.e. communication, management, and strategy. Such conceptualization would lay the foundation for developing communication management as a concept that is useful for empirically exploring the social phenomenon to which it refers.